Stability parameter estimates in upland cotton cultivars evaluated in the Northeast of Brazil - Farias, Francisco José Correia; Ramalho, Magno Antônio Patto; de Carvalho, Luiz Paulo; Moreira, José de Alencar Nunes (Pesquisa Agropecuaria Brasileira, 1996)
Yield data of seed cotton from the 56 experiments of cultivar evaluation were evaluated in the Northeast of Brazil, from 1985 to 1992, seeking to estimate the stability and adaptability parameters as well as to verify whether they are heritable. The method proposed by Silva & Barreto (1985) and modified by Crtiz et al. (1989) was utilized. The repeatability of stability parameters was estimated according to the method utilized by Santos et al. (1982). The cultivars CNPA 3H, CNPA 83-180, CNPA 6H, IAC 20, CNPA 7H and CNPA 85-241 are the most adaptable and stable, while HR 102, BR-1, CNPA Giorge I and CNPA Precoce I are also the most stable, under unfavorable environments, however with low yield. In general, the cultivars express highly predictable performances, except cultivars BR- 1 and CNPA Giorge I, that are unstable and less adaptable. The estimated stability parameters show, in general, high repeatability, proving that it is possible to foresee success with the selection utilizing these parameters.